Assessment of Intestinal Hormones Cholecystokinin and Peptide YY in Iraqi Women with Polycystic Ovarian Syndrome. - Mariam A. Malik; Sura F. Alsaffar (مجلة كلية الطب)
Background: Among the most prevalent hormonal, reproductive and metabolic issues impacting women is polycystic ovarian syndrome. Also, insulin resistance raises the chance of developing chronic illnesses in women with polycystic ovarian syndrome, including diabetes mellitus, cardiovascular disease, metabolic syndrome, and potentially endometrial and breast malignancies. Objectives: Measurement of two intestinal hormones (cholecystokinin, peptide YY), luteinising hormone, follicle-stimulating hormone, and Prolactin. Waist and wrist circumference were measured in centimeters Methods: A sample of polycystic ovarian syndrome women who were referred to the Medical City of Baghdad hospital for management of their infertility were recruited in the current study. Sixty polycystic ovarian syndrome patients were split into two groups based on Body Mass Index: thirty obese polycystic ovarian syndrome women and thirty overweight polycystic ovarian syndrome women. In addition, thirty healthy control women were added as a third group, whose average age was between 20 and 35 years. Polycystic ovarian syndrome in women was diagnosed using two of the three diagnostic criteria: polycystic ovaries in ultrasound, oligo or anovulation, and hyperandrogenism. The investigation ran from October 2023 until January 2024. The investigations of the patient were requested, and all data in the study were added. Results: Obese women with polycystic ovarian syndrome had significantly higher levels of waist circumference 102.75 ±1.45, prolactin 20.48 ±1.43, luteinizing hormone 7.85 ±0.56, Follicle-stimulating hormone 8.41 ±0.38, and lower levels of Peptide YY 45.33±16.62, and cholecystokinin 14.37 ±3.64. Conclusion: Low cholecystokinin and Peptide YY in obese polycystic ovarian syndrome women lead to a rise in appetite, intake of food, an increase in waist circumference, and accumulation of fat in the abdomen.